Sports skills in martial arts - Olga V. Yusupova; Alexander D. Voronin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the concepts of "skill" and "sport skills", which are studied in the framework of various theories: psychology, acmeology, theory of activity, axiology. During the consideration of these theories, the authors identified stages of formation and development of skills. In addition, based on studies of the concept of "skill" from the point of view of various theories, the authors put forward the assumption that this concept is multifaceted. Furthermore, this paper suggests that the problem of sports skills and ways of their formation in the training process is a very important social and psycho-pedagogical task in the field of amateur and professional sports. During the study the authors examined the concept of "martial arts" and justified the purpose of martial arts in order to clarify the concept of "sport skills in the martial arts”. The authors identified the main structural components of the concept of "sport skills" in order to further establish their relationships and build a model of the formation of sports skills martial fighters: physiological, psychological, moral, technical and tactical, cognitive. At first the necessary condition here is the conceptual refinement of the concept of "sport skills in martial arts", which the authors of the article suggest, based on an analysis of the above theories and empirical experience obtained during coaching and competitive activities. Due to the specification of the concept of "sport skills in martial arts" in the future, the authors are planning to develop organizational and pedagogical conditions of formation of sports skills which used exclusively for martial arts (wrestling, judo, sambo, boxing, etc.), based on this concept.